Retinal axon divergence in the optic chiasm: dynamics of growth cone behavior at the midline [published erratum appears in J Neurosci 1995 Mar;15(3):following table of contents] - Pierre Godement; Li‐Chieh Wang; CA Mason (1994)
To study how retinal ganglion cell axons diverge in the optic chiasm, the behavior of dye-labeled fibers was monitored in real time with video microscopy in an isolated preparation of embryonic mouse brain, with a focus on embryonic day 15–16. These real-time studies have revealed the dynamics of the growth of individual retinal axons, especially the tempo of extension and growth cone behaviors during divergence in the chiasm, a model for “decision” regions in developing pathways. Within the chiasm, retinal growth cones extend by saltatory growth, consisting of bursts of rapid advance alternating with pauses in extension. During pauses, growth cone appendages remain motile, and develop asymmetries prior to a change in the axis of growth. In a zone straddling the midline, retinal fibers, irrespective of destination, display long pauses for up to several hours, making small advances and retractions with no net extension. While crossed fibers ultimately progress through the midline, uncrossed fibers from inferior temporal retina develop wide-ranging branched growth cones, and then turn back to the ipsilateral side. Turns are effected by the selective retraction or micropruning of asymmetric foci of motile activity, and by the transformation of a backward-directed filopodium into a new growth cone. The behavior of retinal axons at the midline supports the hypothesis that this locus contains cues important for retinal axon divergence. Moreover, the observations of growth cone kinetics in the chiasm elucidate which growth cone forms seen in static preparations mediate growth cone turning, and suggest a model of axon navigation in decision regions in the intact nervous system.